Study on the performance and mechanism of graphene oxide / polyurethane composite modified asphalt - Tengteng Guo; Zhenxia Li; Yuanzhao Chen; Qingyu Xu; Jing Wang; Lihui Jin (Scientific Reports)
Abstract In order to enhance the aging resistance, high temperature stability and low temperature crack resistance of asphalt pavement materials, 0.06% oxidized graphene (GO) and 12% polyurethane (PU) were used as composite modifiers to modify the base asphalt. The RTFOT test was conducted to evaluate the anti-aging performance of the modified asphalt. The rheological properties of GO/PU composite modified asphalt were evaluated. SEM and FTIR tests were used to analyze the microstructure of GO/PU modified asphalt. The results show that the basic performance of composite modified asphalt meets the requirements and the anti-aging performance is improved. The improvement of rutting factor and frequency scanning master curve shows its better anti-rutting deformation ability. The strain recovery R-value for the composite modified bitumen increased by 20.7% at a stress level of 0.1 kPa, and the unrecoverable creep compliance Jnr decreased by 76.0%, showing excellent viscoelastic properties. The creep stiffness S of composite modified asphalt decreased by 31.2% at−12 °C, indicating that it had good low temperature rheological properties. The surface of the modified composite asphalt is relatively smooth, exhibiting a stable network structure, thus solving the PU segregation problem in the matrix asphalt.The change of infrared spectrum absorption peak shows that reaction between isocyanate groups in polyurethane and aromatic esters in bitumen, GO oxidizes with the-CH functional group in asphalt, and the content of C = C double bond changes during the modification process, indicating that the modification of asphalt by GO and PU is a composite modification based on chemical modification and supplemented by physical modification.